2008
DOI: 10.1103/physrevb.77.180501
|View full text |Cite
|
Sign up to set email alerts
|

Universal thermal and electrical transport near the superconductor-metal quantum phase transition in nanowires

Abstract: We describe the thermal (κ) and electrical (σ) conductivities of quasi-one dimensional wires, across a quantum phase transition from a superconductor to a metal induced by pairbreaking perturbations. Fluctuation corrections to BCS theory motivate a field theory for quantum criticality. We describe deviations in the Wiedemann-Franz ratio κ/σT (where T is the temperature) from the Lorenz number (π 2 /3)(kB/e) 2 , which can act as sensitive tests of the theory. We also describe the crossovers out of the quantum c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
(52 reference statements)
1
26
0
Order By: Relevance
“…30 It can be described by a one-dimensional O(2) LGW theory with Ohmic dissipation. 31,32,33 There is experimental evidence that the pair breaking in this systems is caused by surface magnetic impurities which necessarily also introduce quenched disorder.…”
Section: 17mentioning
confidence: 99%
See 2 more Smart Citations
“…30 It can be described by a one-dimensional O(2) LGW theory with Ohmic dissipation. 31,32,33 There is experimental evidence that the pair breaking in this systems is caused by surface magnetic impurities which necessarily also introduce quenched disorder.…”
Section: 17mentioning
confidence: 99%
“…It is worth noting that Del Maestro et al 33 very recently studied the large-N action (3) in one dimension by numerically solving the saddle-point equations. All their results are in beautiful agreement with our predictions, i.e., they confirmed that the quantum critical point is of infinite-randomness type and in the universality class of the random transverse-field Ising model.…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in fabricating ultra-narrow superconducting nanowires has greatly boosted the interest in studying phase slippage in quasi-one-dimensional superconductors 2 . There has been an intense activity to establish the existence of quantum phase slips (QPS) related to macroscopic quantum tunneling (MQT) [3][4][5][6][7][8][9][10][11] and to study quantum phase transitions between possibly superconducting, metallic and insulating phases in nanowires 4,[12][13][14][15][16][17] . A dissipation-controlled quantum phase transition [18][19][20][21][22][23][24][25] has been predicted in junctions of superconducting nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…(43)), and find exact agreement. After a rather lengthy calculation it was confirmed that perfect correspondence is also found for the thermal conductivity in this limit (61). The concurrence between the two theoretical approaches in this limit is a result of an approximation made in the diagrammatic calculation involving an infinite sum over a class of ladder diagrams which turns out to be equivalent to the large-N limit taken here.…”
Section: Finite Temperature Crossoversmentioning
confidence: 53%